Inhibition of stromal‐interacting molecule 1‐mediated store‐operated Ca2+ entry as a novel strategy for the treatment of acquired imatinib‐resistant gastrointestinal stromal tumors. Issue 9 (28th July 2018) - Yang, Ziyi; Pan, Lijia; Liu, Shilei; Li, Fengnan; Lv, Wenjie; Shu, Yijun; Dong, Ping
Abstract : Imatinib has revolutionized the treatment of gastrointestinal stromal tumors (GIST); however, primary and secondary resistance to imatinib is still a major cause of treatment failure. Multiple mechanisms are involved in this progression. In the present study, we reported a novel mechanism for the acquired resistance to imatinib, which was induced by enhanced Ca 2+ influx via stromal‐interacting molecule 1 (STIM1)‐mediated store‐operated Ca 2+ entry (SOCE). We found that the STIM1 expression level was related to the acquired resistance to imatinib in our studied cohort. The function of STIM1 in imatinib‐resistant GIST cells was also confirmed both in vivo and in vitro. The results showed that STIM1 overexpression contributed to SOCE and drug response in imatinib‐sensitive GIST cells. Blockage of SOCE by STIM1 knockdown suppressed the proliferation of imatinib‐resistant GIST cell lines and xenografts. In addition, STIM1‐mediated SOCE exerted an antiapoptotic effect via the MEK/ERK pathway. The results from this study provide a basis for further research into potential novel therapeutic strategies in acquired imatinib‐resistant GIST. Abstract : Multiple mechanisms are involved in imatinib resistance. Here, we reported a novel mechanism of acquired resistance, which was induced by enhanced Ca 2+ influx through STIM1‐mediated SOCE.